Penguatan Merger Bank Syariah BUMN dan Dampaknya Dalam Stabilitas Perekonomian Negara - Ika Atikah; Maimunah Maimunah; Fuad Zainuddin (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
This study provides an overview of strengthening the merger of state-owned sharia banks, namely BNI Syariah, BSM, BRI Syariah which merged into Bank Syariah Indonesia (BSI). The purpose of the study was to determine the legal arrangements for strengthening the merger of Islamic banks to become BSI and its impact on the stability of state finances during the COVID-19 pandemic. The research method used in this study uses normative research with a statutory approach and a conceptual approach. Primary sources of law use legal regulations related to mergers of banking institutions and secondary sources of law from several kinds of literature such as journals and books relating to the issues being discussed. Meanwhile, legal material analysis techniques are used descriptively. The result of the research is the strengthening of the merger of BUMN Islamic banks starting with the existence of an agreement that is outlined in the written form of an Islamic commercial bank merger agreement as regulated in several applicable legal regulations. The merger of Islamic commercial banks during a pandemic is the right step to maintain the country’s economic stability, as stated in Perpu No.1 / 2020 and POJK No.18 / POJK.03 / 2020. The impact of the merger of Islamic commercial banks, of course, has a positive impact, Indonesian Islamic banks can compete globally by prioritizing more complete services, wider coverage, and better capitalization. For the state, it is certainly a good thing that can be done by the Ministry of BUMN, by initiating the merger of 3 sharia-based state-owned subsidiaries (BNI Syariah, BSM, BRI Syariah) merging into PT. Bank Syariah Indonesia, Tbk. Keywords : Merger, Sharia Banks, Finance